Islamic Marriage Counseling Based on Sharia Principles: A Preventive Solution to Muslim Family Crises - Nurhamidah Hasibuan; Yulia Saputri; Masril Masril (Jurnal Counseling Care, 2026)
This study aims to develop and analyze the effectiveness of an Islamic marriage counseling model based on sharia principles as a preventive and curative approach to Muslim family crises. The research employs a descriptive qualitative method with a case study design involving Muslim couples and Islamic counselors who apply the values of the Qur’an and Sunnah in counseling practice. Data were collected through in-depth interviews, observation, and document analysis, and analyzed using the interactive model of Miles and Huberman. The findings reveal that the application of sharia principles such as sabr (patience), ‘adl (justice), shura (consultation), and rahmah (compassion) leads to meaningful and profound improvements in marital harmony, communication, and spiritual resilience. Sharia-based counseling not only facilitates the resolution of emotional conflicts but also strengthens spiritual awareness and moral responsibility within the household. The integration of Islamic values with modern psychological theories creates a more holistic, contextual, and transformative counseling approach. The results of this study are expected to contribute to the development of Islamic counseling curricula and reinforce the role of counselors as murabbi in nurturing families characterized by sakinah, mawaddah, and rahmah in the modern era.